Microbiology : - Tortora, Gerard J. (Pearson, 2016)
This book came in excellent shape, and I think the cover is awesome! So far, it has helped me a lot in class. As for the content, some chapters (such as 5) explain the mechanisms of Metabolism very concisely. Other chapters (6) seem to be quite wordy. There are many ways of culturing bacterial species, and this book really takes time to explain them. The information can be dense in these parts, and the way the authors transition between topics can seem rushed. Other than that, it's a great study aid and supplement to the lectures for this class.